Identifying Strategies to Reduce Missed Opportunities for HPV Vaccination in Primary Care: A Qualitative Study of Positive Deviants. (October 2020) - Rand, Cynthia M.; Concannon, Cathleen; Wallace-Brodeur, Rachel; Davis, Wendy; Albertin, Christina S.; Humiston, Sharon G.; Szilagyi, Peter G.
The objectives of this study were to assess the contextual factors, practice strategies, and sustainability of interventions implemented during a national quality improvement (QI) project to raise human papillomavirus (HPV) vaccination rates. We conducted semistructured interviews with positive deviant practices that successfully reduced missed opportunities by ≥20% for HPV vaccination in the prior year. We assessed leadership support, motivators, interventions used, and sustainability. Key themes related to QI teams included strong leadership support, multidisciplinary teams, having a practice champion, and a collaborative environment. Themes related to the interventions included using a presumptive bundled recommendation for all appropriate vaccines at age 11, previsit planning, and reminders for preventive visits, which were sustainable for most practices 1-year postintervention. Both internal practice-level factors (multidisciplinary teams, collaboration, and previsit planning) and organizational factors (institutional support and health system–level reminders for preventive visits) were key to a successful QI intervention to improve HPV vaccination.